Discovery of 2, 6-disubstituted pyrazine derivatives as inhibitors of CK2 and PIM kinases. Issue 8 (1st May 2018) - Gingipalli, Lakshmaiah; Block, Michael H.; Bao, Larry; Cooke, Emma; Dakin, Les A.; Denz, Christopher R.; Ferguson, Andrew D.; Johannes, Jeffrey W.; Larsen, Nicholas A.; Lyne, Paul D.; Pontz, Timothy W.; Wang, Tao; et al.
Graphical abstract: Abstract: The design and synthesis of a novel series of 2, 6-disubstituted pyrazine derivatives as CK2 kinase inhibitors is described. Structure-guided optimization of a 5-substituted-3-thiophene carboxylic acid screening hit (3a ) led to the development of a lead compound (12b ), which shows inhibition in both enzymatic and cellular assays. Subsequent design and hybridization efforts also led to the unexpected identification of analogs with potent PIM kinase activity (14f ).